Gestão pública municipal e eficiência administrativa: Uma proposta para a tramitação de atos administrativos para a Prefeitura de Uberlândia - Valentim, Victor Grama (2024)
The interest in new management practices, such as process-based management, has been growing among service organizations, but studies in this field are still in their infancy, especially in the public sector. The adoption of innovative management strategies and systems offers potential for optimizing processes, reducing operational costs, and increasing effectiveness. This dissertation explores the creation and processing of administrative acts with concrete effects within the Executive Branch of Uberlândia, aiming to propose improvements that enhance their efficiency. Through the methodologies of Business Process Management (BPM) and Design Research (DR), the research seeks to map the current process for handling administrative acts with concrete effects within the Executive Branch of the Municipality of Uberlândia, evaluate the vulnerabilities of the current process, and propose, through a technological product, a new process or adjustments in the workflow for these administrative acts to achieve greater efficiency, cost-effectiveness, and agility. This initiative aims to improve public management, making it more effective and with the potential for application in other contexts.